Projeto estrutural de uma colhedora de café operando em terrenos declivosos - Silva, Evandro Pereira da (2018)
This work has as object of study the accomplishment of a structural project of a coffee harvester operating in sloping terrain, due to the importance that this parcel of land present in several regions and also because of the lack of harvester projects that operate in these conditions. The main objective of this work was to obtain project results, when analyzing the structure of a new coffee harvesting machine design, which operates on slopes of 50%. The simulations were performed using software, considering the finite element technique and static analysis, generating results of stresses, displacements, safety factors and reaction forces in the regions of the wheel that composes the structure. A modal analysis was also carried out in order to determine the different natural frequencies that caused displacements in order to avoid the phenomenon of resonance, which amplifies the displacements/deformations of the components. With the use of software simulations, it is possible to predict the working situations of these machines, reducing time and costs with prototype constructions. Thus, the main structural components of the machine were analyzed as the first part of the work, where the harvester was modeled, following some design criteria based on weight, reduced dimensions for better mobility, main characteristics: the modeling and simulation of a threewheel harvester in triangular distribution, upper structure in a triangular shape, 300 mm misaligned vibrating cylinders, maximum height and width of 3,0 m and mainly different heights between the sides of the machine, which allow them to operate on land with up to 50% slope. It was obtained some project results that provided important information for a new simulation, which was performed after the most complete modeling of the harvester and where loads were applied in its structure considering components, such as: full coffee tank, main engine, cylinders vibrators, radiator, fuel tank, horizontal and vertical coffee transportation systems, driver, among others. As a result, a minimum safety factor was obtained within the acceptable values for ductile materials, uneven load distribution between the two right-hand wheels when compared to the left-hand wheel, which presented lower load values on it, suggesting a better distribution of weights between the wheels. The values of displacements were of small intensity, but the values of the displacements, in some given natural frequencies, were considered of great magnitude. In the second part of the study, in which an article was published, twenty modal forms were generated after modal analysis, considering the empty and full coffee harvester's reservoir. The simulations were performed by the finite element method, in which real contour conditions were applied to the motor chassis of the harvester. As a result, regions of the components with stresses above the material flow limit were observed. At the rear of the chassis, greater displacements were also observed, suggesting a new positioning of the rear wheel to obtain uniform load distribution. Some natural frequencies, which present greater displacements/deformations might be achieved by the operation of the main motor associated with the vibrating system in the coffee cup, which may cause failure of components.